The formation and implementation of recovery policy in the regions of Ukraine - Yakovchuk, Yaroslav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article examines the peculiarities of the formation and implementation of recovery policy in the regions of Ukraine and the role of local public authorities in this process.The peculiarities of drawing up recovery and development plans and programmes for comprehensive recovery of regions and the city of Kyiv are analysed. At the same time, considerable attention is paid to the role of military administrations as temporary public authorities. It is noted that the bottom-up principle, a decentralised reconstruction process, should be the basis for the formation and implementation of regional recovery measures, which is the best way to achieve the goals of sustainable development of the region. The Ukraine's experience in restoring the eastern regions is analysed. It is identified the current problems that did not contribute to the achievement of the envisaged measures, and proposes measures to prevent such consequences in the course of formulating the recovery policy, in particular: when formulating recovery plans and programmes, a real assessment of the state of negative impacts and their consequences (damages) on a particular region should be made, priorities should be identified to ensure social justice and welfare of the population, and a list and content of exclusively priority measures should be formed which are not necessary for the           It is concluded that the implementation of recovery measures should be comprehensive, carried out at the appropriate level of coordination between central and regional public authorities with the introduction of monitoring and evaluation of decisions made, which will ensure sustainable policy and sustainable development of Ukraine.  At the same time, the implementation of priority recovery measures directly depends on the actions of the military administration and its interaction with central government agencies, business entities and civil society.